College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 1, Equations and Graphs - Section 1.4 - Solving Quadratic Equations - 1.4 Exercises - Page 123: 36


$3\pm 2\sqrt{2}$

Work Step by Step

We solve using the quadratic formula: $x^{2}-6x + 1 = 0$ $x=\frac{-b\pm\sqrt{b^{2}-4ac}}{2a}=\frac{-(-6)\pm\sqrt{(-6)^{2}-4(1)(1)}}{2(1)}=\frac{6\pm\sqrt{36-4}}{2}=\frac{6\pm\sqrt{32}}{2}=\frac{6\pm\sqrt{16*2}}{2}=\frac{6\pm 4\sqrt{2}}{2}=3\pm 2\sqrt{2}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.